SPSS analysis without anguish : version 15.0 for Windows - Coakes, Sheridan J.; Steed, Lyndall G.; Price, Jennifer Clare (John Wiley & Sons Australia, 2008)
This latest edition of SPSS: Analysis Without Anguish is based on Version 15. 0 of SPSS for Windows. SPSS is a sophisticated piece of software used by social scientists and related professionals for statistical analysis. Always popular in previous editions, the text continues to address the needs of all users of SPSS software.